Manajemen Strategi Pemasaran Pondok Pesantren Mafatihul Hikmah Jati Agung Lampung Selatan - Rokimin Rokimin; Dudun Ubaedullah; Idham Idham; Leni Putri Rusdiana (Mudir : Jurnal Manajemen Pendidikan, 2022)
The development of science and technology as well as the fierce competition of educational institutions at this time requires schools to innovate, and be creative in making marketing strategies. Marketing strategy is one of the keys to the success of an institution in attracting public interest. The problems raised and studied in this study are: 1. How is the marketing promotion strategy carried out by the Mafatihul Hikmah Jati Agung Islamic boarding school, 2. How is the segmentation, targeting, and positioning strategy carried out by the Mafatihul Hikmah Jati Agung Islamic boarding school. This research was conducted at the Mafatihul Hikmah Islamic boarding school, Jati Agung, South Lampung with a qualitative approach. The results showed 1. Marketing promotion strategies at the Mafatihul Hikmah Islamic boarding school used print media (banners), social media (facebook and whatsapp), and word of mouth information. (personal selling). 2. The segmentation strategy applied using a geographical approach, the targeting is schools around Jati Agung, Mafatihul Himah Islamic boarding school positioning with the tahfidz program and habituation programs that are superior.